Analysis of the Staffing Needs Division in a Persero Company Using the Workload Indicator Staffing Needs (WISN) Method - Wedadjati, Ratna Sesotya; Helmi, Sulaiman (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2024)
Purpose – This research aims to find out the needs of employees or human resources at PT PLN UIP Tanjung Jati B Jepara based on the WISN method and find solutions to problems related to employees or human resources from WISN calculations.  Methodology – The workload calculation method at PT PLN UIP Tanjung Jati B uses the WISN (Workload Indicator Staffing Need) workload calculation. Calculations using WISN are easy to do with validity and reliability that have been measured valid and reliable. Originality – This study analyzed human resource needs at one of the large state-owned companies, namely PT PLN Tanjung Jati B Jepara, which was carried out to improve excellent service to the company. Findings and Discussion – The workload using the WISN method, PT PLN UIP Tanjung Jati B Jepara, has a workforce of 81 people. The total number of gaps from the WISN calculation results is 20 people or less than 20 staff. Conclusion – Utilizing the WISN method at PT PLN UIP Tanjung Jati B Jepara highlighted a workforce gap of 20 employees in a total staff of 81. Addressing this gap is essential for optimizing operational efficiency and enhancing service quality. This study underscores the importance of strategic human resource planning to meet organizational demands, ensuring continued success and service excellence at PT PLN Tanjung Jati B Jepara. Keywords: Management, human resource, excellent service,  staffing needs, workload